Rediscovery and revision of Foenobethylus Kieffer, 1913 (Hymenoptera, Bethylidae) - Várkonyi, Gergely; Polaszek, Andrew (Zootaxa, 2007)
The bethylid genus Foenobethylus Kieffer, 1913, unstudied for almost a century, is redescribed and assigned to the subfamily Pristocerinae based on a preliminary phylogenetic assessment. Four new species: F. bidentatus n. sp. (Brunei), F. elongatus n. sp. (Malaysia), F. emiliacasellae n. sp. (Thailand), and F. thomascokeri n. sp. (Malaysia) are described, based on males only, as females remain unrecognised in this genus. All specimens are deposited in the Department of Entomology, the Natural History Museum, London, U.K. The type species F. gracilis Kieffer (Philippines), although unrepresented by any traceable specimen, can be distinguished from these species based on the original description. A key to the five known species of Foenobethylus is provided.